2017
DOI: 10.4103/1319-2442.198152
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mean platelet volume and neutrophil/lymphocyte ratio with inflammation and proteinuria in chronic kidney disease

Abstract: Atherosclerosis, which develops as a result of inflammation, is the most important cause of morbidity and mortality in chronic kidney disease (CKD). In this study, we investigated the relationship of mean platelet volume (MPV) and neutrophil/lymphocyte ratio (NLR) with inflammation and proteinuria in patients with CKD Stage 3-4. Healthy individuals who applied to nephrology clinic for checkup purposes acted as controls. Fifty-three patients and 30 healthy controls were included in the study. Patients with diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This was in agreement with Yilmaz [22] who reported that MPV was lower in patients with CKD compared to healthy individual but this was not statistically significant. Also, Bilen [7] , showed that the study with 200 patients with CKD (50 kidney transplantation, 50 hemodialysis, 50 peritoneal dialysis, 50 and stage 3-4 CKD reported no statistical difference of MPV between all groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was in agreement with Yilmaz [22] who reported that MPV was lower in patients with CKD compared to healthy individual but this was not statistically significant. Also, Bilen [7] , showed that the study with 200 patients with CKD (50 kidney transplantation, 50 hemodialysis, 50 peritoneal dialysis, 50 and stage 3-4 CKD reported no statistical difference of MPV between all groups.…”
Section: Discussionsupporting
confidence: 91%
“…Also, Binnetoglu [34] showed that study in 69 patients with stage 3 and 4 CKD not diabetic or malignant found NLR is a marker with prognostic value for the presence and degree of proteinuria. Also, Yilmaz [22] showed that study in fifty-three stage (3-4) CKD patients and 30 healthy controls. Patients with diabetes mellitus, active infection, malignancy, and coronary artery disease were excluded and found that NLR is high in CKD patients and is correlated with proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MPV was found to be a risk factor for renal function with OR=1.992 ( P =0.005). Some studies have documented the association between MPV and inflammation [48]. The mechanism may be as follows, the heart failure process is also a process of inflammatory, increased inflammatory mediators may affect MPV, then it might induce larger and more reactive platelets [49].…”
Section: Discussionmentioning
confidence: 99%
“…21 It is known that inflammation begins in the early stages of CKD. 7,8 Our study showed an increase in CRP values with the progression of renal impairment and found a statistically significant difference in the values of serum concentration of CRP between all groups of subjects with different stages of CKD. Liu et al have investigated the inflammatory status in subjects with CKD, dividing them into three groups: CKD 1-2, CKD 3-4, and CKD-5.…”
Section: Discussionmentioning
confidence: 48%
“…Published papers report increased levels of CRP in patients with CKD compared with healthy controls. [6][7][8] New hematological inflammatory markers have emerged in the past few years, such as the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR), which increase during chronic inflammation. [9][10][11][12][13][14] Their predictive and prognostic role has been proven in malignancy, hypertension, heart disease, vascular disease, but also CKD.…”
Section: Introductionmentioning
confidence: 99%